Indigenous Traditional Knowledge Used for Reproductive Disorders and Constraints Faced by Small Dairy Farmers - Chandra Verma, Hukum; Dhananajay Singh, Kunwar; Kumar Verma, Manoj; Kumar, Subodh; Kumar, Amit; Kumar, Rajesh (The Indian Journal of Animal Reproduction, 2025)
The present study was conducted by the Department of Veterinary & A.H. Extension Education, ANDUAT Kumar Ganj, Ayodhya on reproductive disorders information was generated from 120 dairy farmers; Majority (87.50%) of farmers in case of prolapsed and other Indigenous Traditional Knowledge (ITK) used are as follows: correct mild prolapsed by themselves using lather shoe, desi ghee and pumpkin, warming of rear part of animal, reduce feeding specially concentrate. Lack of grazing fields (100) was ranked first constraint in the research area faced by small dairy Farmers Abortion, Dystocia and stillbirth were mostly treated by veterinary doctors and remaining reproductive disorders were treated by dairy farmers through by using grains, herbs and other medicinal plant on the basis of ITK